A Different Perspective on the Evolution of UK Income Inequality - Anthony B. Atkinson; Stephen P. Jenkins (Institute of Labor Economics (IZA), 2018)
This paper scrutinizes the conventional wisdom about trends in UK income inequality and also places contemporary inequality in a much longer historical perspective. We combine household survey and income tax data to provide better coverage of all income ranges from the bottom to the very top. We make a case for studying distributions of income between tax units (i.e. not assuming the full income sharing that goes with the use of the household as the unit of analysis) for reasons of principle as well as data harmonization. We present evidence that income inequality in the UK is as least as high today as it was just before the start of World War 2.
Keywords: C46; C81; D31; 330; inequality; tax unit; household; Gini coefficient; income tax data; household survey data